A selection of image processing techniques : from fundamental to research front - Zhang, Yu-Jin, 1954- (Boca Raton : CRC Press, 2022)
"This book focuses on seven commonly used image processing techniques. These are Image de-noising, Image de-blurring, Image repairing, Image de-fogging, Image reconstruction from projection, Image watermarking, and Image super-resolution. For each of these selected techniques, comprehensive coverage is provided"--
Image de-noising -- Image de-blurring -- Image repairing -- Image de-fogging -- Image reconstruction from projection -- Image watermarking -- Image super-resolution.
OCLC-licensed vendor bibliographic record.
Keywords: Image processing -- Digital techniques; COMPUTERS / Computer Science; COMPUTERS / Computer Vision & Pattern Recognition; COMPUTERS / Computer Graphics / Image Processing (see also PHOTOGRAPHY / Techniques / Digital)